2021
DOI: 10.3390/horticulturae7110485
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary Light with Increased Blue Fraction Accelerates Emergence and Improves Development of the Inflorescence in Aechmea, Guzmania and Vriesea

Abstract: In protected cultivation, increasing the light level via supplementary lighting (SL) is critical to improve external quality, especially in periods with low light availability. Despite wide applications, the effect of light quality remains understated. In this study, the effect of SL quality and nutrient solution electrical conductivity (EC) on growth and flowering of three bromeliad species was investigated. Treatments included solar light, and this supplemented with R90B10 [90% red (R) and 10% blue (B)], R80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Plant species conservation necessitates the introduction of commercially valuable taxa into agricultural settings and their sustainable utilization to alleviate the over-harvesting pressure on wild populations [52]. In response to this need, cultivation practices and farming operations ought to be developed and established, predominantly employing an optimized fertilization program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant species conservation necessitates the introduction of commercially valuable taxa into agricultural settings and their sustainable utilization to alleviate the over-harvesting pressure on wild populations [52]. In response to this need, cultivation practices and farming operations ought to be developed and established, predominantly employing an optimized fertilization program.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf coloration depends on the fertilization regime, and affects both photosynthetic capacity and visually perceived quality [52]. In this study, it was assessed by three different methods as follows:…”
Section: Non-destructive Evaluation Of Leaf Coloration At Three Growt...mentioning
confidence: 99%
“…In contrast, R light partitioned more biomass into the root and caused the highest root dry weight to be gained when the biomass of both monochromatic light recipes is compared to the biomass of plants exposed to other light qualities ( Figure 1 and Table 1 ). The alteration of biomass partitioning to different plant organs as a consequence of plant growth in different lighting environments has been reported in diverse plant species such as chrysanthemum [ 30 ], saffron [ 28 , 31 ], bromeliads [ 32 ], and lettuce [ 23 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the findings obtained in the present study, it has been reported that R light is an inducer of shoot growth. In contrast, B light usually restricts biomass allocation to the above-ground parts (especially into the leaves, while it promotes biomass partitioning into the generative organs) [ 32 ]. However, Hernández and Kubota (2016) reported that monochromatic B light caused a dramatic increase in the length of cucumber seedlings compared to other spectra, which follows our results [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following removal of the substrate from the tuber via gentle washing, tuber volume was measured by employing a volume-displacement technique 62 , 63 . Tubers were suspended in a cylinder filled with water, and tuber volume was then determined by measuring the volume of displaced water.…”
Section: Methodsmentioning
confidence: 99%